2018
DOI: 10.3126/jkahs.v1i2.24137
|View full text |Cite
|
Sign up to set email alerts
|

Risk Profile of Uterovaginal Prolapse

Abstract: Introduction: Pelvic Organ Prolapse is a common problem in Nepal. The aim of this study was to assess the magnitude of pelvic organ prolapse and risk factors associated with it. Methods: This hospital based retrospective descriptive study was conducted in gynecological Out Patient Department of College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan from October 2011 and September 2013.The data were retrieved from the records and analyzed. Women who were earlier subjected for surgical correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Two-thirds (40, 66.7%) of respondents had less than two years birth space which was consistent with the findings of study done in Bharatpur Hospital, Chitwan, Nepal that was 66% of respondents resumed work two weeks and 46% of respondents had resumed sexual intercourse within fourth week and 59% of respondents had less than two years birth space. 15 In present study, 32 ( 53.3%) of respondents had adequate food after childbirth which was consistent with the finding that was 70% of respondents had adequate food after childbirth which was consistent with study done in Bharatpur, Chitwan. The study done in Kalikot district, Nepal found that was 39.7% of respondents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two-thirds (40, 66.7%) of respondents had less than two years birth space which was consistent with the findings of study done in Bharatpur Hospital, Chitwan, Nepal that was 66% of respondents resumed work two weeks and 46% of respondents had resumed sexual intercourse within fourth week and 59% of respondents had less than two years birth space. 15 In present study, 32 ( 53.3%) of respondents had adequate food after childbirth which was consistent with the finding that was 70% of respondents had adequate food after childbirth which was consistent with study done in Bharatpur, Chitwan. The study done in Kalikot district, Nepal found that was 39.7% of respondents.…”
Section: Discussionsupporting
confidence: 92%
“…10 In present study, 23 (38.3%) of respondents had smoking history which was similar to study done in Bharatpur, Chitwan, Nepal that was 38.7% of respondents had smoking habit. 15 Similar study done in Manma, Kalikot district showed that 30.4% of respondents had history of smoking. 6 In present study, the association between degree of uterine prolapse and marriage at age of below 20 years where p = 0.004, first childbirth age below 20 years where p = 0.01, higher the number of pregnancy and childbirth is significant association since p = 0.007 respectively, and degree of UP is significantly associated with birth attendant since (p=0.01)which was consistent in finding with study done in Gorkha district, Nepal that showed significant association between degree of UP and birth attendant (p =0.03).…”
Section: Discussionmentioning
confidence: 61%